Filters of floristic exchange: How traits and climate shape the rain forest invasion of Sahul from Sunda. (14th January 2018) - Yap, Jia‐Yee S.; Rossetto, Maurizio; Costion, Craig; Crayn, Darren; Kooyman, Robert M.; Richardson, James; Henry, Robert
Abstract: Aim: To evaluate how biogeographical and ecological processes influenced species distributions and community assembly in a continental rain forest flora with mixed biogeographical origins. Location: Continental Australia. Methods: We identified 795 species with Sahul ancestry (Australian rain forest flora of Gondwanan origin) and 604 species with Sunda ancestry (rain forest plant lineages of Indo‐Malaysian origin) from a total of 1, 872 free‐standing Australian woody rain forest taxa. We then compared the distribution of Sunda to Sahul species in relation to variation in species richness and phylogenetic endemism at continental scale, and local species distributions in available plot data from the Tropics (Cape York and the Australian Wet Tropics in northern Queensland) and subtropics (Nightcap‐Border Ranges, Washpool and Dorrigo, in northern New South Wales). We compared the dispersal and persistence characteristics, and key functional traits (leaf size, fruit size, wood density and maximum height at maturity) of the Sunda and Sahul components of the continental rain forest flora. The influence of climate (temperature) and local environmental (altitude) factors in driving fine‐scale distributional patterns was evaluated. Results: Sunda rain forest species richness decreased with increasing latitude but maintained high levels of endemism, including in the south. Sunda species traits suggest more efficient dispersal and faster growth than Sahul lineages. Resprouting (persistence) was less evident in species with Sunda than Sahul ancestry. We show that Sunda lineage distributions were influenced by interacting environmental and climatic factors, as well as historical contingencies. Main conclusions: Efficient dispersal and relatively fast growth likely facilitated the establishment and spread of Sunda lineages in Australia. However, the Sunda invasion was resisted in stable, saturated communities of Sahul lineages, and in the temperate south where climate acted as a strong filter. The results highlight the importance of integrating historical biogeography and contemporary ecological processes to study continental‐scale rain forest distribution and assembly.